Experimental Politics : Work, Welfare, and Creativity in the Neoliberal Age - Lazzarato, M. (Maurizio) (Book collections on Project MUSE., 2017)
In Experimental Politics, Maurizio Lazzarato examines the conditions of work, employment, and unemployment in neoliberalism's flexible and precarious labor market. This is the first book of Lazzarato's in English that fully exemplifies the unique synthesis of sociology, activist research, and theoretical innovation that has generated his best-known concepts, such as'immaterial labor.'The book (published in France in 2009) is also groundbreaking in the way it brings Foucault, Deleuze, and Guattari to bear on the analysis of concrete political situations and real social struggles, while making a significant theoretical contribution in its own right. Lazzarato draws on the experiences of casual workers in the French entertainment industry during a dispute over the reorganization ('reform') of their unemployment insurance in 2004 and 2005. He sees this conflict as the first testing ground of a political program of social reconstruction. The payment of unemployment insurance would become the principal instrument for control over the mobility and behavior of the workers. The flexible and precarious workforce of the entertainment industry prefigured what the entire workforce in contemporary societies is in the process of becoming: in Foucault's words, a'floating population' in 'security societies.' Lazzarato argues further that parallel to economic impoverishment, neoliberalism has produced an impoverishment of subjectivity -- a reduction in existential intensity. A substantial introduction by Jeremy Gilbert situates Lazzarato's analysis in a broader context.